SEMANTIC ANALYSIS IN ENGLISH HIGH SCHOOL HANDBOOKS - salmia - syarifuddin; Irmawaty - Hasyim (British : Jurnal Bahasa dan Sastra Inggris, 2020)
This paper aims to uncover semantics meaning found in the literary work in the English handbook of high school using a semantic approach. This study applied a descriptive qualitative method. The data in this study were phrases, sentences, and clauses that allegedly contain implicit and explicit meanings. The literary work analyzed were taken from three (3) handbooks for high school student. The results of the study showed the discovery of various types of semantic meanings in literary works found in the English handbook as teaching materials. The types of semantics meaning found in the English Handbook for high school were literal and non-literal meaning. These meanings did not appear together in one literary work, but it is spread in the literary works found in the English handbooks.